Health information technology use in clinical practice and implications for implementation: Examples from Canberra Health Services, Australia - Chelsea Liu; Rosemary Wyber; Uday N. Yadav; Rohan Essex; Paul Dugdale (Health Information Management Journal, 2026)
Background: Health information technology (HIT) has advanced rapidly over the past two decades, yet digital transformation in healthcare remains difficult and lags behind many other sectors. Existing literature suggests that implementation outcomes are context-dependent and may vary across settings, limiting the feasibility of universal standardisation. Objective: Building on this broader literature, this study examines three contrasting HIT implementations at Canberra Health Services (CHS), Australia, to address three questions: (i) How do clinicians perceive the benefits and limitations of these technologies, and what shared implementation challenges emerge across cases? (ii) What explains the variation in implementation outcomes across the three cases? (iii) What do these findings imply for how HIT implementation and development should be conceptualised and evaluated? Method: This study was conducted at CHS, the public health service provider in the Australian Capital Territory, using a multiple qualitative case study design. It examined three HIT initiatives: WhatsApp use for hospital work-related communication, MedChart for inpatient medication management, and My Health Record use to support access to shared patient information across emergency, specialist outpatient and primary care settings. The interview guide was informed by actor–network theory. Data were collected through 18 in-person semi-structured interviews conducted in 2021–2022. Results: Across the cases, long-standing challenges related to data quality, privacy and security persisted, including concerns about data completeness, consistency and access control. However, the main barrier to integration was continued reliance on traditional communication practices, resulting in hybrid workflows. Rather than transitional, these hybrids were embedded in routine work, limiting interoperability and integration. Despite generally positive user attitudes, outcomes varied with levels of user engagement, closely linked to technical effectiveness and workflow fit. This highlights HIT’s sociotechnical interdependence and the often-underestimated role of technical design in shaping engagement and behavioural change. Overall, impact was uneven: neither investment nor adoption alone predicted better outcomes, indicating a non-linear relationship between these metrics and realised benefits. Conclusion: Realised benefits from HIT do not necessarily follow directly from implementation or uptake alone, but are shaped by interactions between technology, existing practices and organisational context. Implications for health information management practice: HIT success should be assessed not only by uptake, technological sophistication or investment, but by how effectively technologies integrate with workflows, support interoperability and generate context-appropriate impact.